The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1021/acsomega.9b02877
|View full text |Cite
|
Sign up to set email alerts
|

Screening of a Glycopolymer Library of GM1 Mimics Containing Hydrophobic Units Using Surface Plasmon Resonance Imaging

Abstract: Effective screening methods for the development of glycopolymers as molecular recognition materials are desirable for the discovery of novel biofunctional materials. A glycopolymer library was prepared to obtain guidelines for the design of glycopolymers for the recognition of cholera toxin B subunits (CTB). Glycopolymers with varying ratios of hydrophobic and sugar units were synthesized by reversible addition fragmentation chain transfer polymerization. N-tert-Butylacrylamide, N-phenylacrylamide, and N-cyclo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…The hydrophobicity of the functional groups of the co-monomers was quantified by the log P value, and the SPRI signals of the glycopolymers with 20% hydrophobic monomers for CTB showed a correlation with the log P values ( Figure 4 ). 15 This suggested that the hydrophobic groups with log P values higher than 0.15 exhibited a cooperative effect in binding to the pockets of CTB, resulting in enhanced interactions on the glycopolymer-immobilized surface. However, the correlation between the SPRI signals and the log P values was not observed for a lower co-monomer incorporation ratio (10%) due to the insufficient amount for the interactions with the binding pockets of CTB ( Figure S4 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The hydrophobicity of the functional groups of the co-monomers was quantified by the log P value, and the SPRI signals of the glycopolymers with 20% hydrophobic monomers for CTB showed a correlation with the log P values ( Figure 4 ). 15 This suggested that the hydrophobic groups with log P values higher than 0.15 exhibited a cooperative effect in binding to the pockets of CTB, resulting in enhanced interactions on the glycopolymer-immobilized surface. However, the correlation between the SPRI signals and the log P values was not observed for a lower co-monomer incorporation ratio (10%) due to the insufficient amount for the interactions with the binding pockets of CTB ( Figure S4 ).…”
Section: Resultsmentioning
confidence: 99%
“…The mixture of glycomonomer (GalAAm), AAm, and each hydrophobic monomer (EthylAAm, NIPAm, TBAm, ButylAAm, CyHexAAm, and PhAAm) were polymerized using PET-RAFT polymerization as per previous studies. 15 Setting the monomer concentration to 0.5 M, the monomers, RAFT agent (MCEBTTC), and photocatalyst (ZnTPP) were dissolved in DMSO (200 μL) at a molar ratio of 100:1:0.02. The mixtures of various monomer compositions were put in wells of the 96-well plate and were irradiated by LED lights (λ = 527 nm) at room temperature for 5 h. The conversion rates were determined by 1 H NMR, and the relative molecular weights and polydispersity index were calculated by gel permeation chromatography analysis.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We assume that this difference is due to the sugar display on a flexible, cylinder backbone that supports extended structures and thus cross-linked aggregates form. The greater hydrophobicity of the norbornene-based glycopolymers may also play an important role in the binding of CTB to glycopolymers …”
Section: Resultsmentioning
confidence: 99%
“…The greater hydrophobicity of the norbornene-based glycopolymers may also play an important role in the binding of CTB to glycopolymers. 42 To explain the trend we observed, we propose the model system shown in Figure 5. In this system, the ligands of the glycopolymer point radially outward to maximize surface tension (Figure 1B).…”
Section: ■ Results and Discussionmentioning
confidence: 99%